Indikator Lingkungan Intern Pada Kinerja Keuangan Dengan Intellectual Capital Dan Size Sebagai Variabel Moderasi Dan Mediasi - FETY ROCHYAWATI (Jurnal Perilaku dan Strategi Bisnis, 2017)
The purpose of this study was to determine whether there the effect of trust, participation, strategic relevance towards financial performance, to determine whether firm size able to mediate the relationship between trust, participation, strategic relevance with financial performance and to determine whether intellectual capital able to moderate the relationship between trust, participation, strategic relevance with financial performance.The research sample consisted of 60 respondents manufacturing industry. The methodof data collectionis done using purposive random sampling. The methodof hypothesis testingused is bivariate regression analysis, mediation regression dan regression moderation.The result of this study showed that there the effect between trust and participation towards financial performance, while strategic relevance can not affect financial performance. Firm size not able to mediate the relationship between trust and strategic relevance with financial performance, while the relationship between participation with financial performance able mediated firm size. The relationship between trust, participation, strategic relevance with financial performance not able strengthened with intellectual capital.